Automated Performance Regression Analysis: An Industrial Case Study - Fagerström, Mikael; Ismail, Emre Emir (My University, 2016)
Along with the technological developments and increasing competition there is a major incentive for the companies to produce and market high quality products before their competitors. In order to conquer a bigger portion of the market share companies have to ensure the quality of the product in a shorter time frame. To accomplish this task companies try to automate their test processes as much as possible. It is critical to investigate and understand the problems that occur during di erent stages of test automation processes. This thesis is conducted as a case study and presents challenges regarding automatically analysing non-functional test results and provide improvement suggestions based on interviews at a large company in Sweden. The key contributions of this work are lling the knowledge gap in research for the performance regression test analysis automation and providing warning signs and a road map for the industry.
Keywords: Data- och informationsvetenskap; Computer and Information Science